Contexto productivo y comercial del aguacate en Colombia (2020)
Total plantings: 21 698 ha (25% Hass). 1100 ha of Hass currently in production. More Hass will be in production by 2011. Total production: 220 000 t p.a. of which 13 000 t is currently Hass (only 300 t of organic Hass). Imports from Venezuela and Ecuador: 15 000 t p.a. (Sylvester, common, criollo). Per capita consumption in Colombia: 4,2 kg p.a. Avocado is part of the Colombian diet. Expected growth: 1 200 ha Greenskins. 1200 ha Hass. Hass is generally harvested from January to May, but some areas can harvest year-round. Domestic market prices (farm gate): US$ 0.7 – 1.0. Promotion: Between 2010-2011 US$ 200,000 (growers and government) will be spent domestically US market access: PRA for Hass is currently in process.